Advancements and challenges in scalable modular antenna arrays for 5G Massive MIMO networks - Ashraf, Arselan; Gunawan, Teddy Surya; Kartiwi, Mira; Nur, Levy Olivia; Nugroho, Bambang Setia; Astuti, Rina Pudji (IEEE, 2024)
This paper presents a comprehensive review of the advancements and challenges in scalable modular antenna arrays for 5G Massive MIMO (Multiple Input Multiple Output) networks, a pivotal technology for the next-generation wireless communication. Tracing the evolution of wireless technologies from 1G to 4G, the paper contextualizes the paradigm shift brought by 5G, characterized by enhanced spectral efficiency, massive device connectivity, and higher frequency bands. Focusing on Massive MIMO, the paper explores its role in augmenting network capacity and signal quality via advanced techniques like beamforming and spatial multiplexing. It delves into the intricacies of designing and implementing scalable modular antenna arrays, essential for the flexibility and optimization of rapidly evolving 5G networks. The review also covers mathematical modeling, advantages of Massive MIMO, and the challenges in integration, performance under diverse conditions, and cost-complexity balance. Concluding with insights into the commercialization trajectory of MIMO technology and its integration into modern telecommunications, the paper highlights the ongoing research directions and future potential of scalable modular antenna arrays in meeting the ambitious demands of 5G and beyond.